Regional variation in courage and entrepreneurship: The contrasting role of courage for the emergence and survival of start‐ups in the United States. Issue 5 (10th February 2019) - Ebert, Tobias; Götz, Friedrich M.; Obschonka, Martin; Zmigrod, Leor; Rentfrow, P. Jason
Abstract: Objective: There is growing evidence that certain regional personality differences function as important drivers of regional economic development (e.g., via effects on entrepreneurship and innovation activity). The present investigation examines the impact that regional variation in the trait courage has on entrepreneurship. Method: Using data from a new large‐scale internet‐based study, we provide the first psychological map of courage across the United States ( N  = 390, 341 respondents from 283 U.S. metropolitan regions). We apply regression analyses to relate regional courage scores to archival data on the emergence and survival of start‐ups across American regions. Results: Our mapping approach reveals comparatively high levels of regional courage in the Eastern and Southern regions of the United States. Regional courage scores were positively related to entrepreneurial activity, but negatively related to start‐up survival—even when controlling for a wide variety of standard economic predictors. Several robustness checks corroborated these results. Finally, regional differences in economic risk‐taking accounted for significant proportions of variance in the relationship between regional courage and entrepreneurship. Conclusion: Our results suggest that regional courage may contribute to a pattern of enterprising and also risky economic behavior, which can lead to high levels of entrepreneurial activity but also shorter start‐up survival.